Cross-sectional and longitudinal association between accelerometer-measured light-intensity physical activity and cognitive function in older adults - Jhan, Jing-Han; Chen, Jiaren; Lai, Ting-Fu; Park, Jong-Hwan; Liao, Yung (Frontiers in Aging Neuroscience, 2025)
ObjectivesRegarding the methods of improving cognitive function in older adults, it is well-established that moderate-to-vigorous physical activity (MVPA) is beneficial. Considering the safety and mobility of older adults, recent research has focused on the benefits of light-intensity physical activity (LPA) on cognitive function. However, limited research has utilized the different domains of cognitive examination scales [such as the Mini-Mental State Examination (MMSE)] to analyze the relationship between LPA and different domains of cognitive function and compare the cross-sectional and longitudinal results. Thus, this study aimed to investigate the cross-sectional and longitudinal association between LPA and both overall and domain-specific cognitive function in older Taiwanese adults.MethodsThis longitudinal study recruited participants in an outpatient department of geriatrics and gerontology in a medical center in Taipei City, Taiwan. Data was collected from September 2020 to 2021; the follow-up data were collected until December 2022. Participants were community-dwelling older adults aged ≥ 65 years who could walk independently. Baseline physical activity (any bodily movement produced by skeletal muscles that requires energy expenditure) and sedentary behavior (any waking behavior while in a sitting, reclining or lying posture with low energy expenditure) were measured with a GT3X+ triaxial accelerometer, categorized as sedentary behavior (< 100 counts/min), LPA (100–2,019 counts/min) and MVPA (≥ 2,020 counts/min). Cognitive functions were measured using the Chinese version of MMSE for the baseline and follow-up data. Binary logistic regression analysis was used to examine the association between 3 h/day of LPA and cognitive functions. Baseline dependent variables were whether participants had overall cognitive impairment and whether scores of domain-specific MMSE were at the maximum level; in the follow-up analysis, the dependent variables were whether overall and domain-specific scores of MMSE maintained or increased (obtained by subtracting the baseline from the follow-up overall and individual domain MMSE scores).ResultsA total of 167 participants were included (52.10% female; 76.11 ± 6.47 years). The cross-sectional analysis results indicated that in the adjusted model (adjusted for age, sex, educational degree, wear time, MVPA time, and sedentary behavior time), both overall and domain-specific cognitive functions were not significantly associated with ≥ 3 h/day of LPA. The longitudinal analysis results indicated that in the adjusted model, ≥ 3 h/day of LPA was significantly negatively associated with the maintenance or increase of language [odds ratio (OR): 0.88; 95% confidence interval (CI): 0.01–0.99; P = 0.049], and significantly positively associated with the maintenance or increase of orientation (OR: 3.83; 95% CI: 1.01–14.46; P = 0.048).ConclusionThe cross-sectional and longitudinal impacts of engaging in ≥ 3 h/day of LPA on cognitive functions differed. While engaging in ≥ 3 h/day of LPA has no significant short-term benefits, performing ≥ 3 h/day of LPA is beneficial for maintaining or improving orientation cognitive function in long term. Further studies should explore the longitudinal relationship between LPA and orientation cognitive function to provide a more comprehensive understanding of their potential interactions.